Incidence of injury in South African male youth footballers from an elite football academy - Dawood, M. A.; Mostert, K.; Bester, M. J. (South African Journal for Research in Sport, Physical Education and Recreation, 2021)
The incidence and characteristics of injury within a population of South African male youth football players from an elite academy was determined. A cross-sectional epidemiological study design including 63 male youth footballers, aged 14-19 years, selected for the squad of an elite South African academy for the 2017 football season. A pre-season baseline demographic questionnaire was administered. All injuries were recorded throughout the 2017 competitive season using the FIFA F-MARC Injury Questionnaire. The total injury incidence was 36.4 injuries per 1000 exposure-hours. Match and training incidences were 39.6 and 34.7 injuries per 1000 exposure-hours respectively. The Under-17 team recorded the highest injury incidence, with the Under-19 team recording the lowest. Injuries most commonly occurred in the lower leg and ankle with contusions and muscle strains/ruptures being the most common. The majority of match injuries occurred due to contact with another player and most training injuries were overuse injuries. Age and previous football academy experience did not influence injury incidence in this population. Further research on larger study populations is required to determine if these results are representative of the South African elite male youth football population.